2023
DOI: 10.1101/2023.04.09.536155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root-exuded secondary metabolites can alleviate negative plant-soil feedbacks

Abstract: Plants can suppress the growth of other plants by modifying soil properties. These negative plant-soil feedbacks are often species-specific, suggesting that some plants possess resistance strategies. However, the underlying mechanisms remain largely unknown. Here, we investigated if and how benzoxazinoids, a class of dominant secondary metabolites that are exuded into the soil by maize and other cereals, help plants to resist negative plant-soil feedbacks. We find that three out of five tested crop species sup… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…More recently, Gfeller et al (2023b) showed that wheat plants grown in the field on soil conditioned by a maize genotype capable of releasing root benzoxazinoids had more reproductive tillers, leading to higher grain yield. Root-emitted benzoxazinoids have also been shown to increase maize resistance to negative PSF (Gfeller et al, 2023a). These studies demonstrate the important role of the soil biota and belowground chemical interactions in mediating PSF.…”
Section: Integrating the Soil Metabolome Into Psf Researchmentioning
confidence: 73%
“…More recently, Gfeller et al (2023b) showed that wheat plants grown in the field on soil conditioned by a maize genotype capable of releasing root benzoxazinoids had more reproductive tillers, leading to higher grain yield. Root-emitted benzoxazinoids have also been shown to increase maize resistance to negative PSF (Gfeller et al, 2023a). These studies demonstrate the important role of the soil biota and belowground chemical interactions in mediating PSF.…”
Section: Integrating the Soil Metabolome Into Psf Researchmentioning
confidence: 73%
“…Plant–soil feedbacks are well known to depend on the environmental context, the responsible mechanisms are, however, only partly understood (Gfeller, Thönen, et al, 2023; van der Putten et al, 2013; Smith‐Ramesh & Reynolds, 2017). Plant nutrient supply, for example, can influence the outcome of plant–soil feedbacks in crops and wild plants (Kos et al, 2015a; Kuerban et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They are long known to be involved in allelopathy and defence against insects and pathogens (Niemeyer, 2009; Schandry & Becker, 2020). More recently, they have been shown to alleviate plant growth‐suppressive effects provoked by preceding plants (Gfeller, Thönen, et al, 2023). They can also chelate iron and aluminium (Hu, Mateo, et al, 2018; Zhao et al, 2019; Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This process may also feedback to shape the microbial community by influencing the accessibility of iron to rhizosphere microbes. DIMBOA is in turn degraded to MBOA (3), which is the most abundant benzoxazinoid in the maize rhizosphere due to its greater stability (Hu et al, 2018;Gfeller et al, 2024, this issue of New Phytologist, pp. 2575-2588.…”
Section: Interactions Between Chemical Defenses Soil Microbes and Nut...mentioning
confidence: 99%
“…1). In a paper published in this issue of New Phytologist, Gfeller et al (2024;2575-2588 demonstrate that the production of benzoxazinoids can protect maize plants from heterospecific PSFs associated with several cover crops commonly grown in rotation with maize (Gfeller et al).…”
mentioning
confidence: 99%